Monitoring the elimination of human African trypanosomiasis: Update to 2014. - José R Franco; Giuliano Cecchi; Gerardo Priotto; Massimo Paone; Abdoulaye Diarra; Lise Grout; Raffaele C Mattioli; Daniel Argaw (PLoS Neglected Tropical Diseases)
Background The World Health Organization (WHO) has targeted the elimination of Human African trypanosomiasis (HAT) 'as a public health problem' by 2020. The selected indicators of elimination should be monitored every two years, and we provide here a comprehensive update to 2014. The monitoring system is underpinned by the Atlas of HAT. Results With 3,797 reported cases in 2014, the corresponding milestone (5,000 cases) was surpassed, and the 2020 global target of 'fewer than 2,000 reported cases per year' seems within reach. The areas where HAT is still a public health problem (i.e. > 1 HAT reported case per 10,000 people per year) have halved in less than a decade, and in 2014 they corresponded to 350 thousand km2. The number and potential coverage of fixed health facilities offering diagnosis and treatment for HAT has expanded, and approximately 1,000 are now operating in 23 endemic countries. The observed trends are supported by sustained surveillance and improved reporting. Discussion HAT elimination appears to be on track. For gambiense HAT, still accounting for the vast majority of reported cases, progress continues unabated in a context of sustained intensity of screening activities. For rhodesiense HAT, a slow-down was observed in the last few years. Looking beyond the 2020 target, innovative tools and approaches will be increasingly needed. Coordination, through the WHO network for HAT elimination, will remain crucial to overcome the foreseeable and unforeseeable challenges that an elimination process will inevitably pose.